Utilization of Google Sites Application in Improving Short Story Writing Skills of Grade IX Students of SMP Swasta Amalia Medan - Titin Mariani; Wisman Hadi; M. Surip (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
This research is motivated by students' lack of interest in reading short stories because learning resources and learning media that are interesting and interactive are limited or inadequate. This causes the interaction is not well established between students and teachers in learning. Thus resulting in low learner ability in writing short stories. Learners need learning media to help teaching and learning activities in the classroom so that learning is more varied. This study aims to describe the utilization of Google Sites learning media in learning short stories. The research method in this study is descriptive qualitative with an emphasis on case study research. The data analysis techniques used were descriptive analysis techniques carried out to assess the characteristics of a data using an analysis model and the results of written tests carried out in the form of pre-test and post-test scores for writing short stories. The subjects of this study were ninth grade students at SMP Swasta Amalia Medan as many as 36 students. The results prove that learning short story text using Google Sites media can improve students' short story writing skills. This is evidenced by the comparison of the students' pre-test average score of 72.33 increased to 88.44.